The Relationship between MACC1/c-Met/Cyclin D1 Axis Expression and Prognosis in ESCC - Yan Shi; Meng-Yan Li; Hui Wang; Chao Li; Wen-Ying Liu; Yong-Mei Gao; Bo Wang; Jia-Wei Song; Yu-Qing Ma (Analytical Cellular Pathology)
Background. Esophageal cancer is one of the most common malignant tumors of the digestive system, with high incidence and mortality. Methods. Immunohistochemical method was used to detect the expression of MACC1, c-Met, and cyclin D1 in ESCC and its adjacent tissues. Statistical analysis was done by SPSS 23.0. Results. The high expression of MACC1 and cyclin D1 was significantly correlated with tumor size. High c-Met expression was associated with patient ethnicity. MACC1 expression was positively correlated with both c-Met and cyclin D1. c-Met expression was also positively correlated with cyclin D1. Patients with high expression of MACC1 and c-Met had worse OS; patients with high c-Met expression also had worse PFS. Conclusion. MACC1, c-Met, and cyclin D1 proteins are closely related to the occurrence and development of esophageal squamous cell carcinoma. MACC1 may affect the prognosis of ESCC by regulating the expression of the c-Met/cyclin D1 axis.